(untitled) (ModaPalavra e-periódico, 2018)
This is an interview with the professional Paula Abbas, Head of Strategic Design and teacher in Coolhunting and Design Thinking, about the work of a coolhunter and the study of trends as a strategy of innovation in companies. The interviewee discusses the importance of researching trends from the professional point of view, the abilities of the coolhunter and the methodology and influence of globalization and digital technology in the research of trends. Finally, she comments on the changes in the fashion segment and predicts where this market is heading.